Implementing Peer Tutoring Method in Developing Students’ Speaking Skills - Fijar Nur Fitria; Didih Faridah; Rachmawati Etika (Journal of English Education Program (JEEP), 2026)
This study investigates the implementation of the Peer Tutoring method in developing students’ speaking skills within one of the English communities in Tasikmalaya. This research applied a qualitative case study approach which involved questionnaires and semi-structured interviews to explore two main questions: (1) how Peer Tutoring enhances students’ speaking skills, and (2) how it influences their confidence in speaking English. The findings reveal that Peer Tutoring significantly improves students’ speaking abilities, particularly in vocabulary, pronunciation, fluency, and confidence. Most participants reported feeling more comfortable and motivated in peer-led sessions compared to traditional classroom settings. Moreover, peer tutors benefited from improved public speaking and leadership skills, while peer learners gained confidence and practical speaking experience in a supportive environment. Despite some challenges, such as nervousness and initial communication barriers, both tutors and tutees adapted and showed progress over time. The study concludes that Peer Tutoring is an effective, collaborative strategy that supports both linguistic and personal development in English as a Foreign Language (EFL) context. The future research are recommended to conduct the broaden research. Further research is recommended to conduct broader research from various aspects, such as different methodological approaches to gain deeper insights.